Miscommunication as a Cause of Disputes in the Relationship Between Doctors and Patients in Hospitals - Endang Kusuma Astuti; Endang Wahyati Yustina; Anisah Che Ngah (Universitas Negeri Semarang, 2025)
This study aims to analyze how miscommunication between doctors and patients in medical services can lead to medical disputes. Employing a sociolegal research approach with qualitative methods, data was collected through in-depth interviews and participatory observations in educational, government, and private hospitals in Semarang City. Patient samples were randomly selected, while doctors were chosen using purposive sampling. Data analysis followed the interactive model of Miles and Huberman, involving data reduction, data presentation, and conclusion drawing. The results reveal that miscommunication often stems from the gap between patient expectations and the reality of medical services, exacerbated by cultural and language differences. Factors such as a lack of openness, empathy, and humanistic two-way communication also contribute. In conclusion, miscommunication is a primary cause of disputes between doctors and patients, highlighting the crucial role of improved communication in preventing conflict and fostering a more trusting and effective healthcare environment.